Chilli paste processing using high-pressure and conventional approaches - Nor Khaizura, Mahmud Ab Rashid; Pratama, Arkan Binatara; Chorng, Phang Kin; Mohamad, Azizah (Hasanuddin University Department of Food Science and Technology, 2025)
This study presented a comparative analysis between chilli paste processed using high-pressure processing (HPP) and traditional thermal treatment (TT) to assess their influence on bioactive attributes, physicochemical properties, and safety. Five distinct processing parameters were examined: untreated (control), HPP at 200, 400, and 600 MegaPascals (MPa), respectively, treated for 6 minutes, and TT at 80°C for 10 minutes. Significant differences (p<0.05) were observed between HPP and TT across most physicochemical properties and all bioactive constituents, barring the hue angle (h), Aw, and pH. HPP-treated samples closely resembled the control in terms of physicochemical and bioactive characteristics. Notably, HPP at 400 MPa yielded the highest concentrations of ascorbic acid (AA), cumulative phenolic compounds (CPC), and radical scavenging activity (RSA). Conversely, HPP at 600 MPa exhibited the most robust pungency properties, as reflected by capsaicin (CAP), dihydrocapsaicin (DHC), and Scoville heat units (SHU). TT samples had the most microbial inactivation, although a 5-log reduction level was not reached. Bacillus cereus (ATCC 14579) count, total plate count (TPC), and yeast and mould count (YMC) reductions are intensified at higher HPP pressures. HPP applied at 400-600 MPa for 6 minutes was deemed superior in maintaining quality compared to TT, while also retaining safety levels. In summary, HPP proves to be a proficient technique for processing chilli paste, with minimal disruption to its physicochemical and bioactive attributes. HPP at 400-600 MPa for 6 minutes is a promising alternative, offering both quality preservation and safety advantages over traditional methods.